دور الفضاء الرقمي للعملDWS في تحسين الخدمات الإدارية دراسة ميدانية بكلية العلوم الإنسانية والاجتماعية بجامعة المسيلة - نسيمة مزراق; اشراف: عاشور علوطي (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة الى التعرف على دور الفضاء الرقمي للعمل DWS في تحسين الخدمات الإدارية لدى مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة، ولتحقيق أهداف الدراسة اعتمدنا المنهج الوصفي، كما قمنا بتطبيق أداة استبيان مصممة من طرفنا على عينة قصدية مكونة من (70) مستخدما بالكلية، وبعد المعالجة الإحصائية للبيانات أسفرت النتائج عما يلي: • يساهم الفضاء الرقمي للعمل DWS في تحسين سرعة وكفاءة الخدمة الإدارية لدى مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة. • يساهم الفضاء الرقمي للعمل DWS في تحسين التواصل والتفاعل بين مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة . • يساهم الفضاء الرقمي للعمل DWS في تحقيق الشفافية والمصداقية في الخدمة الإدارية لدى مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة. • يساهم الفضاء الرقمي للعمل DWS في تحديث الخدمات الإدارية لدى مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة . • يساهم الفضاء الرقمي للعمل DWS في تسهيل وتوضيح الخدمات الإدارية لدى مستخدمي كلية العلوم الإنسانية والاجتماعية بجامعة المسيلة . الكلمات المفتاحية: الفضاء الرقمي للعمل DWS، الخدمة الإدارية، المستخدمين Abstarct : This study aimed to identify the role of the Digital Workspace (DWS) in improving administrative services for users of the Faculty of Humanities and Social Sciences at the University of M'sila. To achieve the study's objectives, we adopted a descriptive approach. We also applied a questionnaire designed by us to a purposive sample of (70) users at the faculty. After statistical processing of the data, the results yielded the following: • The Digital Workspace (DWS) contributes to improving the speed and efficiency of administrative services for users of the Faculty of Humanities and Social Sciences at the University of M'sila. • The Digital Workspace (DWS) contributes to improving communication and interaction between users of the Faculty of Humanities and Social Sciences at the University of M'sila. • The Digital Workspace (DWS) contributes to achieving transparency and credibility in administrative services for users of the Faculty of Humanities and Social Sciences at the University of M'sila. • The Digital Workspace (DWS) contributes to modernizing administrative services for users of the Faculty of Humanities and Social Sciences at the University of M'sila. • The Digital Workspace (DWS) contributes to facilitating and clarifying administrative services for users of the Faculty of Humanities and Social Sciences at the University of M'sila. Keywords: Digital Workspace (DWS), Administrative Service, Users